Shallow reservoirs in urban perimeter: evaluation of trophic status and relations with the zooplanktonic community - Martins, Heytor Lemos [UNESP]; Panarelli, Eliana Aparecida; Borges, Jaqueline Souza; Korasaki, Vanesca; Millan, Rodrigo Ney (FapUNIFESP (SciELO), 2024)
Aim: The zooplankton community is used as a bioindicator of environmental changes and can be an indicator of trophic status in aquatic environments through changes in the composition of the community. The objective of this work was to study the variation of shallow reservoir systems in an urban park, evaluating the relationships between physical, chemical, and biological variables. Methods: The collections were conducted monthly for a year in the surface of reservoirs. The physical and chemical variables of the water were measured using a multiparametric probe on the surface. Nutrient analysis was performed using spectrophotometry in the laboratory. Zooplankton was collected using a plankton net (60 µm mesh size). Principal Coordinate Analysis (PCoA) was used to verify whether the three reservoirs present differences in zooplankton community composition. Results: Altogether, 43 taxa belonging to 16 families were collected. Rotifera was the most representative group, with 27 taxa, Cladocera had 13 taxa, and Copepoda had only three taxa. The environmental variables indicated different trophic status between the reservoirs, demonstrating greater eutrophication in reservoirs 1 and 3. An association between the composition of the zooplankton community and the trophic state of the reservoirs was verified. Conclusions: The composition of the zooplankton community shows differences among three of the shallow urban reservoirs studied. Reservoir 1 exhibited Filinia terminalis and Asplanchna herrick as indicator species. As for reservoir 2, with a lower trophic status, the indicative species were Bosmina freyi and Diaphanosoma polyspina, correlated with lower concentrations of nitrate, nitrite, total phosphorus, pH, and lower values of electrical conductivity. Reservoir 3 exhibited Brachionus angularis and Brachionus calyciflorus as indicator species, demonstrating a similar nutrient profile to R1, but with higher nitrate concentrations.
Reservatórios rasos em perímetro urbano: avaliação do estado trófico e relações com a comunidade zooplanctônica
Keywords: bioindicator; Cladocera; Copepoda; Rotifera